EFFECTIVENESS OF THE MODULE ON KNOWLEDGE AND MOTIVATION REGARDING PAP SMEAR EXAMINATION AMONG WOMEN OF REPRODUCTIVE AGE - Umi Sukowati; Ulfia Fitriani Nafista; Lailil Fatkuriyah; Ainul Hidayati (Universitas Kusuma Husada Surakarta, 2026)
Background: Screening is central to global cervical cancer control; however, no district/city in East Java has yet reached the screening target. Participation in Pap smear screening is influenced by multiple determinants, particularly behavioral factors linked to women’s knowledge and motivation; therefore, health education is expected to promote positive behavior change.Methods: This study used a quasi-experimental, one-group pretest–posttest design in Lumajang Regency, East Java, Indonesia, conducted from August 2024 to January 2025. Purposive sampling recruited 63 women from a local community group. The intervention consisted of a structured educational module provided to all respondents. Knowledge and motivation were measured before and after the module using validated questionnaires. Results: The statistical analysis applied to this research was the Wilcoxon signed-rank test for non-normally distributed variables, with α = 0.05. Mean knowledge increased from 8.60 (min 5; max 10) at pretest to 9.57 (min 9; max 10) at posttest. Motivation to undergo Pap smear screening also improved, with mean scores increasing from 23.15 at pretest to 43.95 after the intervention. Shapiro–Wilk tests indicated non-normality for both knowledge and motivation (p < 0.05); thus, Wilcoxon tests were used. Significant differences were observed for knowledge (p < 0.001) and motivation (p < 0.001). Conclusion: These findings suggest that module-based health education effectively strengthens women’s knowledge and motivation to participate in Pap smear screening in settings where overall screening coverage remains below the target.